2011
DOI: 10.1016/j.schres.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The MCCB impairment profile for schizophrenia outpatients: Results from the MATRICS psychometric and standardization study

Abstract: The MATRICS Psychometric and Standardization Study was conducted as a final stage in the development of the MATRICS Consensus Cognitive Battery (MCCB). The study included 176 persons with schizophrenia or schizoaffective disorder and 300 community residents. Data were analyzed to examine the cognitive profile of clinically stable schizophrenia patients on the MCCB. Secondarily, the data were analyzed to identify which combination of cognitive domains and Publisher's Disclaimer: This is a PDF file of an unedite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
166
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(191 citation statements)
references
References 25 publications
16
166
3
6
Order By: Relevance
“…Recursive partitioning is a data-mining technique that uses decision trees to predict outcomes from predictor variables (28)(29)(30). In particular, this methodology facilitates exploration of complex and potentially overlapping predictor variables and is better suited than regression analyses for studies with large numbers of predictors versus sample size (28,29).…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recursive partitioning is a data-mining technique that uses decision trees to predict outcomes from predictor variables (28)(29)(30). In particular, this methodology facilitates exploration of complex and potentially overlapping predictor variables and is better suited than regression analyses for studies with large numbers of predictors versus sample size (28,29).…”
Section: Analysesmentioning
confidence: 99%
“…Branching continued until there was no further improvement in correct differentiation of participants by outcome, a process that aimed to simplify a complex set of potential predictor variables into a few simple "if-then" rules that predicted outcomes (28)(29)(30). Given our large number of predictor variables versus sample size, we used a tenfold cross-validation approach (31,32), splitting our sample into ten random groups of approximately equal size to approximate the analysis of a different sample drawn from the consumers of this supported housing program (28).…”
Section: Analysesmentioning
confidence: 99%
“…Effects of gender varied more between individual tests. A recent follow-up study of this sample showed that the speed of processing and the social cognition domains best distinguished individuals with schizophrenia from the community sample [42]. The speed of processing, visual learning and attention/vigilance domains best distinguished individuals with schizophrenia who were competitively (i.e.…”
Section: Matrics Co-norming and Validationmentioning
confidence: 87%
“…Schizophrenia is associated with pervasive cognitive impairment which encompasses perception, attention, processing speed, working memory, learning, social cognition and motor control (29,30). In patients, measures of global cognitive performance or intelligence are reduced about two thirds of a standard deviation from those of gender-and age-matched nonpsychiatric groups.…”
Section: Cognitive Remediationmentioning
confidence: 99%